(untitled) (Journal of Bangladesh Academy of Sciences, 2022)
Identification and quantification of aflatoxins; B1, B2, G1, and G2 in twenty different rice samples were done by high-performance liquid chromatography coupled with a fluorescence detector. The rice samples were extracted with aqueous methanol and the extract was purified by immunoaffinity column by following the officially recognized ISO 16050 method. A post column derivatization device (Kobra cell) was used to make Bromo-derivative of the aflatoxins. The method for analysis of aflatoxins in the rice sample was validated in terms of selectivity, linearity, sensitivity, and recovery. Calibration curves were linear with a coefficient of variation r2 ≥ 0.9998, 09997, 0.9956, and 0.9969 for B1, B2, G1, and G2, respectively. The limit of detection (LOD) was 0.009, 0.006, 0.039, and 0.025 μg kg-1 and the limit of quantification (LOQ) was 0.025, 0.018, 0.116 and 0.075 μg kg-1 for B1, B2, G1, and G2, respectively. Recoveries (n=4) were carried out at two different spiking concentrations (1.39 and 2.77 μg kg-1 for B1, 0.49 and 0.98 μg kg-1 for B2, 1.56 and 3.12 μg kg-1 for G1 and 0.51 and 1.01 μg kg-1 for G2) and were ranged from 56.71±1.60-70.37±5.59%, 57.71±0.58-75.36±6.77%, 65.53±0.73-72.85±5.93% and 65.83±2.92-99.20±3.16% for B1, B2, G1, and G2, respectively. Aflatoxin B1, B2, G1, and G2 in rice samples were found to be present at 70, 60, 40, and 10%, respectively. The total aflatoxins (B1, B2, G1, and G2) in the rice samples were found to be in the range of trace- 3.54 μg kg-1. The results revealed that 18 out of 20 samples contained the detectable number of aflatoxins. The total aflatoxins content was found to be below the tolerance level (4 μg kg-1) according to the European Union (EU). So, the rice samples were safe for consumption, but the major concern is that a large population, especially in rural areas, consumes rice three times a day. If the rice sample contained aflatoxins even, below the present tolerance limit, there is a possibility of bad health implications from the consumption. J. Bangladesh Acad. Sci. 45(2); 187-196: December 2021